Estudo citogenético em aranhas (Mygalomorphae e Araneomorphae) com ênfase na evolução dos genes de DNA ribossômico - Gimenez-Pinheiro, Tatiana [UNESP] (2015)
The order Araneae possesses 45,741 taxonomically described species, which are distributed in two suborders, Mesothelae and Opisthothelae, 114 families and 3,965 genera. The cytogenetic data in this order are scarce, considering that less than 2% of the species were studied up to now. Among the 114 families of Araneae, in 45 there are no species cytogenetically examined. In the spiders, the diploid number ranged from 2n♂=7 to 2n♂=128, with sex chromosome system of the simple (X0 and XY) or multiple (X1X20, X1-X130, X1X2Y e X1-X7Y) types, and chromosomes with meta/submetacentric or subtelo/telocentric morphology. In relation to specific chromosome sites, such as the nucleolar organizer regions (NOR), only 30 species were investigated mainly through silver impregnation. In Mygalomorphae and Araneomorphae, the NORs were predominantly located in the terminal region from one to three autosomal pairs. However, in some species, the NORs occurred in the X sex chromosome. Considering the cytogenetic particularities observed in Araneae and the scarcity of information of specific chromosome regions, the purpose of this work was to establish the mechanism of chromosome evolution in Mygalomorphae and Araneomorphae spiders with the focus of the rDNA genes. The chromosome analyses were accomplished with standard staining, silver nitrate impregnation (Ag-NOR) to identify the active NORs and fluorescent in situ hybridization (FISH) to locate the 18S rDNA genes. The 17 species examined here belong to three families of Haplogynae, five of Entelegynae and three of Mygalomorphae. Mitotic metaphase cells exhibited 2n♂=16+X1X2Y in Sicarius cariri and Sicarius ornatus and 2n♂=18+XY in Sicarius tropicus, with Ag-NORs on the terminal region of pair 1. In S. ornatus and S. tropicus, the FISH technique showed similar results to Ag-NOR, but in S. cariri, the ribosomal cistrons were located in the terminal region of the X1 sex chromosome. The description of a ...